2016
DOI: 10.4172/2165-7386.1000258
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care: Supporting Adult Cancer Patients in Ibadan, Nigeria

Abstract: Over 70% of adult cancer patients present late to hospital in Nigeria with devastating consequences. Yet, structured palliative care is only an emerging service in this country with population of over 160 million.Objective: To describe activities of the Ibadan palliative care group and review one year holistic care programme offered by the team to support patients and their families. Methodology:A retrospective study reviewed treatment notes of patients that were enrolled from January to December 2013. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…[ 6 ] Several studies have reported inadequate funding, limited availability of morphine, religious and cultural meaning-making, insufficient PC professionals, and inadequate professional and public knowledge of PC to be factors that have impacted on PC development in Nigeria. [ 7 8 9 10 11 ] Considering that PC is poorly developed in Nigeria,[ 12 ] there is a need for a nuanced and sophisticated understanding of the organizational culture, because this could reveal either cultural enablers or inhibitors that may be drawn upon, or eliminated, to improve PC practice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Several studies have reported inadequate funding, limited availability of morphine, religious and cultural meaning-making, insufficient PC professionals, and inadequate professional and public knowledge of PC to be factors that have impacted on PC development in Nigeria. [ 7 8 9 10 11 ] Considering that PC is poorly developed in Nigeria,[ 12 ] there is a need for a nuanced and sophisticated understanding of the organizational culture, because this could reveal either cultural enablers or inhibitors that may be drawn upon, or eliminated, to improve PC practice.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have uncovered obstacles to PC in an African context, such as too few health professionals with PC training and education; lack of training opportunities; poor knowledge of, and attitudes toward, PC; professionals and service-users' lack of awareness; inadequate opioids; lay meaning-making of cancer/care; and a lack of PC policies in most African countries. [4][5][6][7][8][9] The rising costs of chemotherapy, drug resistance, and insufficient radiotherapy machines are some of the recognized challenges of cancer care in poorly resourced countries. 10,11 In addition, patients with cancer experience not only physical problems but also cancer-related social difficulties that impact on their mental health and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer treatments such as radiotherapy and chemotherapy are not generally available in the public health system [18]. Palliative care such as community/home care for people with advanced stage cancer is also not generally available [19].…”
Section: Discussionmentioning
confidence: 99%